Intimate Pragmatics Language: Subjectivity and Gender - Povinelli, Elizabeth A. (Revista Estudos Feministas, 2016)
This paper discusses metapragmatic and psychoanalytic understandings of language, gender and desire. It discusses the challenge each disciplinary approach to language, gender and desire poses to the other. It argues that a robust theory of language and gender necessitates we view subjectivity as an order of phenomenon distinct from semantic and pragmatic orders of linguistic phenomena. The paper suggests two modest proposals as a way of beginning to understand the interrelationship between language and subjectivity. It begins with a very brief overview of contemporary linguistic anthropological approaches to gender and sexuality. It then describes the intimate pragmatics of speaking-subjects by articulating recent work in metapragmatics and gender with a psychoanalytically inspired account to subjectivity and desire.